Tinjauan Hukum Syar’i terhadap Operasi Plastik: Antara Kebutuhan Medis dan Estetika - Lilita Efquany; Itsnaini Nur Hidayah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study comprehensively examines the concept of Sharia law by highlighting the main divisions within Islamic law: taklifi law and wadh'I law. Taklifi law encompasses five normative categories: obligation, recommendation, permissibility, makruh, and prohibition, which serve to regulate individual behavior in accordance with Sharia principles. Meanwhile, wadh'iy law emphasizes the causes, conditions, and requirements for the validity of a legal act, thus forming a normative framework that guarantees the validity of an action from an Islamic legal perspective. This study uses a normative approach through a literature review of primary sources of Islamic law, such as the Qur'an, Hadith, and classical and contemporary fiqh literature. The results of the study indicate that the division between taklifi and wadh'iy law is crucial for understanding the structure and complexity of Sharia law, both in terms of the vertical relationship between humans and God and the horizontal relationships between individuals. This study also examines the contemporary issue of plastic surgery from an Islamic legal perspective. Plastic surgery is permissible for medical purposes, such as reconstruction following an accident, congenital defect, or impaired bodily function, as it aligns with the principles of preserving benefit and eliminating harm. However, plastic surgery solely for aesthetic purposes is considered forbidden, as it constitutes altering God's creation without a sharia (Islamic) justification. This finding confirms that the division of sharia law is not merely theoretical but also relevant in addressing modern issues, including in medical practice, and has important implications for the development of contemporary Islamic law and its application within the national legal context.